A Nordic harmonisation effort concerning atmospheric dispersion modelling for real-time accident situations. (1st January 2000) - Tveten, U.
Neighbouring countries have often chosen different atmospheric dispersion prognosis models for use in emergency situations. This may result in differences in the predictions, which in turn can lead to the authorities adopting different countermeasures. In a Nordic project within the Nordic Nuclear Safety Research Programme (NKS), a Nordic harmonisation and comparison effort was initiated in the programme period 1991 to 1994, with subsequent follow-up activities. The five Nordic countries (Denmark, Finland, Iceland, Norway and Sweden) have chosen five different medium to long-range models for atmospheric dispersion calculations in emergency situations. The models were tested and compared in four Nordic exercises, which were followed by meetings. The exercises revealed an urgent need for harmonisation in the manner in which the results of calculations are presented during an emergency. Differences in the manner of results presentation by different institutions performing predictions, may lead to misunderstandings, confusion, and stress.